The Effect of Hydrogen Reduction Temperature On The Palladium-Supported Catalyst In The Combustion Of Methane - Nasri, Noor Shawal; Mohsin, Rahmat; Mustafa, Azeman (Penerbit UTM Press, 2000)
The effect of hydrogen reduction temperatures was investigated using